Home fever management in children: a systematic review - Yuniati, Faiza; Erwin, Erwin; Shobur, Sherli; Ardianty, Septi; Sutrisno, Sutrisno (International Journal of Public Health Science (IJPHS), 2025)
Fever is a prevalent illness among children. Physical cooling interventions worsen the child’s condition as a result of parents’ anxiety and misconceptions about fever. This study aims to identify parental physical cooling intervention as fever management for feverish children in the scientific literature. The study adhered to the guidelines in the preferred reporting items for systematic reviews and meta-analyses (PRISMA). The investigations were conducted within scientific electronic databases: ProQuest, PubMed, Scopus, EBSCO, Google Scholar, and Cochrane, published in English, from January 2013 to August 2023. Authors screened articles for inclusion. After exclusion, there were ten studies included in the analysis with 15,488 participants. The literature review demonstrated that the physical cooling methods employed for home fever management were taking off excess clothes, providing extra fluid, warm compresses, sponging, showering and environmental measures. Sponging techniques and cold compresses are popular among parents. However, the methods have negative effects and are not recommended. Effective fever management optimizes the body's physiological response by ensuring adequate hydration, nutrition, and a conducive environment. When the fever worsens, parents should consider seeking medical treatment.